Giant Uterine Fibroid by Giant Uterine Leiomyoma: A Case Report and Literature Review - Maanongun, Michael Tyodoo; Ornguze, Andrea Avershima; Ojo, Babarinde (Disease and Health Research: New Insights Vol. 5, 2024)
The present case report discusses giant Uterine Fibroid by Giant uterine leiomyoma. The most frequent benign gynecologic tumor of the female pelvis is uterine leiomyoma, which develops from uterine smooth muscle. Giant fibroids, on the other hand, are extremely uncommon in modern treatment and provide management difficulties. A 28-year-old nulliparous woman presented in a private clinic in Makurdi, Benue State, Nigeria with severe pain and a slow-growing abdominal mass with pressure symptoms due to a giant uterine fibroid. Laboratory analysis showed a blood haemoglobin concentration of 8.6 g/dL. The remainder of her laboratory results were within normal limits, and pregnancy was excluded. Transabdominal ultrasonography revealed a large hypoechoic mass originating from the uterus. Intraoperatively, the mass was huge, weighed 11.6 kg, was continuous with the uterus and tightly occupied the abdominal cavity with restricted mobility. Myomectomy was done after consideration of the patient’s wishes, fertility concerns and intraoperative findings. The patient did well without complications and was discharged on day six. She got married eight months later, got pregnant six months after marriage and delivered a baby boy through caesarean section nine months later.